ANALISIS KINERJA DALAM PERSPEKTIF POLICAL ECONOMY OF ACCOUNTING (STUDI KASUS PDAM MAJU) - Bambang Haryadi (InFestasi, 2015)
In the process, gain or loss PDAM has been a key indicator in assessing the performance of a company. The impact of this understanding is that many companies are doing financial engineering in order to look good financial performance. As a public company, the performance of PDAM Maju can not be assessed only from a financial point of view only. Need to understand the performance of PDAM Maju from a more meaningful perspective in order to obtain a more thorough understanding of the performance.Analysis tools of critical accounting that uses the framework of Political Economy of Accounting (PEA) aimed to understand and evaluate the role of accounting in the context of economic, social and political. Losses incurred during the company is described as fatamurgana. It seems the company suffered losses , but the actual loss is not the case in real terms. The company's performance is always influenced by various political factors and the lack of the role of power companies